The Relationship between Religion and Entrepreneurship in an Islamic Perspective - Ade Faizin; Holilur Rahman; Muhammad Edi Gunawan; Aminullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper discusses the relationship between religions, especially Islam and entrepreneurship. Entrepreneurship is considered an important pillar for economic development in developing countries. From an Islamic perspective, religion emphasizes the importance of working hard and entrepreneurship as a form of worship to Allah. Various studies have shown that religion influences entrepreneurial activity, both in terms of attitudes, processes and behavior of entrepreneurs. Religious values ​​such as integrity, honesty, and responsibility are a strong foundation for entrepreneurs in building successful and sustainable businesses. On the other hand, religiosity can also provide motivation and inspiration for entrepreneurs in running their businesses. This paper concludes that religion, especially Islam, has an important role in encouraging and shaping entrepreneurial activity. A deep understanding of the relationship between religion and entrepreneurship can contribute to the development of more meaningful entrepreneurship and have a positive impact on society.